The Relationship between Self-Efficacy and Professional Support towards HOTs with the Readiness towards HOTs Pedagogy - Abdul Rahman, Sumaiyah; Abdul Rahman, Shukran; Othman, Dzulfazli (Cambridge Scholars Publishing, 2019)
Teacher self-efficacy plays significant role in determining the effectiveness of high-order thinking (HOT) pedagogy, including for the teaching of science and mathematic subjects. Although teachers have been found to adopt HOT-based exercises, and were ready to implement HOT-based teaching, little is known on whether both would enhance their self-efficacy. The purpose of this paper is to present findings of a research which studies the relationship between Self-efficacy to teach Higher Order Thinking Skills and the availability of Professional support to teach HOTS with the student teachers’ readiness towards HOTS Pedagogy. HOT-based exercises usage, HOT-Implementation readiness, and self-efficacy among science and mathematic student teachers in Malaysia. A group of 121 student teachers have been randomly selected to participate in the study. They responded to three scales which measure their usage of HOT-based exercises, readiness in HOT-Implementation, and self-efficacy. It has been found that the student teachers have high levels of Self-efficacy, readiness and professional support towards HOTS. It has also been found that there were significant relationships between self-efficacy and Readiness towards HOTS Pedagogy.; and between Professional support towards HOTS and Readiness towards HOTS Pedagogy. Significance: The findings provide an account of student-teachers’ readiness in using HOT-based exercises, and their self-efficacy to engage HOT-based exercises. The finding is expected to inform policy makers on the ways to strengthen the training of HOT-based education method among student teachers in the country.